Machine Maintenance Planning Using the Reliability Centered Maintenance (RCM) Method at PT Perkebunan Nusantara XIV Camming Sugar Factory in Bone Regency - Sulkifli, Sulkifli; Lantara, Dirgahayu; Hafid, Muhammad Fachry; Mahendra, Kresna Adi (Omnia Tempus, 2022)
Purpose: Frequent damage to the mill roll machine at the mill station and the absence of special attention to scheduling repairs, this research is expected to make scheduled maintenance intervals and maintenance strategies for mill roll machines at the mill station to reduce downtime and anticipate sudden downtime on the machine. Design/methodology/approach: This study uses the Reliability Centered Maintenance (RCM) method approach to create the most efficient maintenance program by eliminating unnecessary maintenance activities, reducing overhaul frequency, minimizing downtime, minimizing the risk of sudden failure, focusing maintenance on critical components, and improving component reliability. Findings: The results of this study show that there are two strategies used in mill roll machine maintenance, namely preventive maintenance, and corrective maintenance. Research limitations/implications: This study focuses on critical components that often experience damage to the mill roll machine, namely standard milk check, feeder roll, scrapper, and chute components, and does not consider the cost aspect. Practical implications: The results of this study provide input to the company's interval time scheduling and machine maintenance strategy. Originality/value: This research was conducted in the production department of the milling station at PT Perkebunan Nusantara XIV Camming Sugar Factory in Bone Regency, where the production results include white crystal sugar, blotong, and molasses. Research to analyze machine reliability, minimize downtime and propose maintenance schedules and SOPs for maintaining production machinery at Camming Sugar Factory.